PENGARUH EVALUASI KEBIJAKAN PUBLIK, BIAYA SAMBUNG PADA MINAT MASYARAKAT DALAM PEMANFAATAN AIR BERSIH - Purwanto, Eko; Ritonga, Kirmizi; Karneli, Okta (Jurnal Ilmu Administrasi Negara, 2018)
Influence of Public Policy Evaluation, Cost of Connecting to Public Interest in Clean Water Utilization. This study aims to analyze the influence of public policy evaluation and cost connections on the interest of the community in the utilization of clean water. The population of the study was 1,199 family heads with 92 KK samples using slovin formula. This research uses quantitative approach. Data collection techniques through interviews and questionnaires. Technique of data analysis through Test Validity, Reliability Test, Normality Test, Linearity Test, Classic Assumption Test, Significance Test. Based on the results of research, evaluation of public policy and cost connections to the interests of the community simultaneously yield the coefficient of determination of 0.170. This means that the influence of public policy evaluation and cost of simultaneous connection to public interest is 17% while the rest is influenced by other factors.